PENGEMBANGAN DAN PENDAMPINGAN SISTEM INFORMASI PENGOLAHAN PENDAPATAN JASA PADA PT. DMS KONSULTAN BANDAR LAMPUNG - Rohmat Indra Borman; Iqbal Yasin; Muhammad Adam Putra Darma; Imam Ahmad; Yusra Fernando; Agus Ambarwari (Universitas Teknokrat Indonesia, 2020)
PT DMS Konsultan Bandar Lampung is a company engaged in tax consulting services from cooperation with companies to calculate how much obligations the company must pay. Currently processing income data by recording by the administration in the income book. This has resulted in several problems, including resulting in a higher error rate, if data is needed again it will take time to search the data and risk damage and loss of data. For this reason, community service is carried out by developing an information system for processing income data and providing training to employees regarding how to use the application.